Wczesnośredniowieczny handel niewolnikami w bałtycko-orientalnej strefie wymiany w świetle znalezisk kajdan I kłódek - Stanisławski, Błażej; Musin, Aleksander (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
Slavery was common in early medieval Europe with the so-called Baltic-Oriental exchange systemas one of the most important markets. There is a view that the slave trade is difficult to detect in material sources. Shackles are the most characteristic determinant of the slave trade. Shackles were believed to have been a very rare find. However, searching for new materials in old collections and publications turns out to be very productive. The greatest concentration of finds of shackles occurs in the Northwest Slavic region. Shackles were also discovered in other Baltic locations. Moreover, a number of finds have been recorded in Eastern Europe, in two areas to be more exact. The first is the Bulgarian Khaganate, and the other is the Khazar Khaganate. However, shackles are not the only material determinant of the slave trade. Analyses show that iron padlocks were also an element of shackles. They occur in large numbers in many locations in the Baltic zone and in Eastern Europe. Based on the concentration of the shackles and padlocks, seven areas of the slave trade can be identified. The areas of concentration of finds may reflect slave trade centres, mainly clustered around the junctions of the Baltic-Oriental exchange system.